2021
DOI: 10.1063/5.0049284
|View full text |Cite
|
Sign up to set email alerts
|

VO2 nanostripe-based thin film with optimized color and solar characteristics for smart windows

Abstract: This study presents a structuration approach to reach a high luminous transmittance (Tlum) and solar modulation efficiency (ΔTsol) of thermochromic vanadium dioxide (VO2) thin films. Before starting optical simulations, we confirm that the optical properties of monoclinic VO2 continuous films deposited by reactive magnetron sputtering show a good correspondence with numerical results. Then, calculations on ordered VO2 nanostripes demonstrate an enhanced transmittance due to the presence of vertical openings, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…15) Although the MIT property of VO 2 films cannot compare with that of single-crystals, they can stand many reversible SPT cycles, so VO 2 films are widely investigated as the functional materials in electrical switches, smart windows, storage devices, uncooled microbolometers, and thermal diodes. [16][17][18][19][20] The performances of VO 2 films rely on their MIT features, which were found to relate to defects, grain sizes, boundaries, and textured morphologies. [21][22][23][24] Our recent study showed that crystalline orientations might have an apparent effect on the MIT of the VO 2 films over quartz glasses, obtained from a controllable thermal oxidation of V-riched films in a vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…15) Although the MIT property of VO 2 films cannot compare with that of single-crystals, they can stand many reversible SPT cycles, so VO 2 films are widely investigated as the functional materials in electrical switches, smart windows, storage devices, uncooled microbolometers, and thermal diodes. [16][17][18][19][20] The performances of VO 2 films rely on their MIT features, which were found to relate to defects, grain sizes, boundaries, and textured morphologies. [21][22][23][24] Our recent study showed that crystalline orientations might have an apparent effect on the MIT of the VO 2 films over quartz glasses, obtained from a controllable thermal oxidation of V-riched films in a vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Nano/microstructured engineering surfaces, with either rigid or irregular structures, can wavelength-sensitively interact with incident photons to regulate their electromagnetic field distribution at the surface or interfaces, resulting in drastic differences from conventional planar coating surfaces. For VO 2 -based energy-efficient windows, various specially designed structures at the nano- and microscales have been developed, to suppress the surface reflection, , enhance the luminous transmittance and solar energy modulation ability, ,, optimize color, , and regulate the localized surface plasma. , …”
Section: Vanadium Dioxidementioning
confidence: 99%
“…A summary of thermochromic performance for VO 2 film with multilayer structures is shown in Table 3. For VO 2 -based energy-efficient windows, various specially designed structures at the nano-and microscales have been developed, to suppress the surface reflection, 213,214 enhance the luminous transmittance and solar energy modulation ability, 212,215,216 optimize color, 217,218 and regulate the localized surface plasma. 219,220 Long et al explored three different types of nanogrid structures with square holes, circular holes, and circular holes in a hexagonal arrangement to optimize the optical properties by a 3D finite-difference time-domain (FDTD) method.…”
Section: Multilayer Structuresmentioning
confidence: 99%
“…Driven by structural changes from insulating monoclinic (M) at low temperature to metallic rutile (R) at temperatures above the transition temperature ( T c ), this phenomenon involves great optical and electronic changes. This makes this material especially advantageous for thermochromic smart window applications. These appealing properties of VO 2 have also been exploited for a wide range of photonic, optoelectronic, and electronic phase-change devices on silicon platforms, such as optical modulators and limiters, infrared (IR) photodetectors, , or optical , and electrical switches. Likewise, the VO 2 /Si system is also considered a potential candidate for its application as a passive intelligent radiator for spacecraft thermal control .…”
Section: Introductionmentioning
confidence: 99%